The Case of Climate Change Adaptation in Campeche, Mexico : Uncertain Future, Robust Decisions - World Bank (Washington, DC, 2014)
This documented case of climate change adaptation in Campeche Mexico grapples with a problem that is fundamental to addressing climate change risks in areas of high vulnerability, which is how to reach consensus and take decisions under an uncertain future. The state of Campeche in Mexico, is used as an example. With its long coastline, Campeche is highly vulnerable to current and projected future climate threats. Two different approaches to decision making under uncertainty have been explored. (i) A Strategic Environmental Assessment (SEA) approach was used to systematically analyze expected impacts, identify and agree on a menu of adaptation measures, and prioritize those measures, using a powerful combination of solid scientific knowledge and local expertise. (ii) The real options theory approach was applied to selected adaptation alternatives, and the benefits of waiting were compared with the costs of delaying decisions. In general, options that were modular and flexible were found to lead to more robust and prudent adaptation measures. The specific results obtained in this work are less important than the overall tenor and spirit of the messages from these exercises. Most importantly both exercises SEA and real options demonstrated that involved actors are ultimately consistent and cautious in their approach to climate risks. An important lesson to emerge from this work is that there is merit in adopting multiple approaches to tackle problems where uncertainty looms large. When the answers converge there is likely to be greater confidence in the outcomes. A second and perhaps more important lesson is the need to identify all costs including the options foregone by embarking on an irreversible course of action.